Mathematical Models of Exoskeleton Dynamics, Strength, Control - Borisov, Andrey Valerievich; Chigarev, Anatoly Vlasovich; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book presents the current state of the problem of describing the musculoskeletal system of a person. Models of the destruction of the endoskeleton and the restoration of its functions using exoskeleton are presented. A description is given of new approaches to modeling based on the use of weightless rods of variable length with concentrated masses. The practical application to the tasks of numerical simulation of the movements of the musculoskeletal system of a person is described. Exoskeleton models with variable-length units based on absolutely hard sections and sections that change their telescopic type length have been developed. The book is intended for specialists in the field of theoretical mechanics, biomechanics, robotics and related fields. The book will be useful to teachers, as well as graduate students, undergraduates and senior students of higher educational institutions, whose research interests lie in the modeling of anthropomorphic biomechanical systems.
Introduction -- Statistical Model Of Destruction Of A Human Musculoskeletal System -- Problems Of Strength At Loading Multilayer Bones Of The Human -- Modeling The Dynamics Of An Anthropomorphic Mechanism With Eleven Movable Links Of Variable Length -- Using Angles Calculated Between the Links to Simulate the Human Movement in Passive-Active Exoskeleton with Spring Elements of Two Types.
Keywords: Robotics; Biomedical engineering; Mechanical engineering; Robotics; Biomedical Engineering and Bioengineering; Mechanical Engineering; Musculoskeletal system -- Mathematical models; Human mechanics -- Mathematical models; Robotic exoskeletons; Biomechanical Phenomena; Exoskeleton Device; Robotics